Sensing Characteristics of Side-Hole Fiber-Based Long-Period Grating - Yi Xin; Xinyong Dong; Junwei Yuan; Yi Li; Shangzhong Jin; Sulei Zhang (Advances in Materials Science and Engineering)
Long-period gratings (LPGs) have been fabricated in a side-hole fiber (SHF) by using a pulsed CO2 laser. Sensing characteristics of this SHF-LPG to temperature surrounding refractive index and bend have been investigated. Experimental results show that resonant wavelength of the SHF-LPG has a blue shift with temperature with sensitivity of −0.11 nm/°C, a blue shift with increasing sensitivity with surrounding refractive index ranging from 1.335 to 1.44 (the maximum sensitivity is achieved when the surrounding refractive index reaches the effective index of the fiber cladding), and a red shift with bend-direction-dependent sensitivity up to 9.36 nm/m−1.